Basics of Functional Echocardiography in Children and Neonates - Cécile Tissot; Vincent Muehlethaler; Nicole Sekarski (Frontiers Media S.A., 2017)
Functional echocardiography has become an invaluable tool in the pediatric and neonatal intensive care unit. "Point-of-care," "target," or "focus" echocardiography allows bedside cardiac ultrasound evaluation of the hemodynamic status of the patient, helps in directing treatment, thus improves patients care. In order to be able to perform functional echocardiography, it is essential to understand the principles of ultrasound, to know the echocardiographic equipment and settings necessary to acquire the images. This article focuses therefore on the basics of cardiac ultrasound. It is meant to give an overview of two-dimensional echocardiographic views, M-mode imaging and Doppler echocardiography for neonatologists and pediatric intensivists. It is richly illustrated for better understanding with some examples of clinical applications of functional echocardiography in the intensive care setting.